A phenomenological model for bubble coalescence in confined highly porous media. (August 2018) - Serres, Marion; Maison, Timothée; Philippe, Régis; Vidal, Valérie
Highlights: A porous medium in a microchannel does not affect the upstream Taylor frequency. Taylor-like and modulated regimes are not due to a feedback effect of the medium. The regime transition is due to bubble coalescence and channelling. A phenomenological model accounts for the flow regimes observed experimentally. Abstract: In a recent work, Serres et al. (2016) considered the stability of Taylor bubbles entering a confined highly porous medium (open cell solid foam of 96% porosity). This experimental work pointed out that a periodic alternation of gas bubbles and liquid slugs in a millichannel can either keep its regularity, or be destructured at the porous medium entrance. A critical bubble length was proposed as a transition parameter between the two observed regimes. This study presents two key results which complement the previous work and explain the regime transition. (1) The comparison of the Taylor flow upstream the porous medium with the Taylor flow in an empty millichannel demonstrates that the regime transtion is not due to the possible feedback of the foam on the upstream flow. (2) A phenomenological model is proposed, which accounts for the observed bubble coalescence and gas channelling in the porous medium in the range of parameters explored in the experiments.